Modelling CAR export from Slovakia to the United Kingdom: Vector error correction approach - Renáta Pitoňáková (Review of Economic Perspectives, 2019)
The aim of the article is to identify determinants of export of road vehicles from Slovakia to the United Kingdom. The Error correction model is based on monthly data from January 2008 to November 2018. The modelling identifies short and long-run effects of real effective exchange rate, inflation rate and industrial production on foreign demand of transport equipment. The real effective exchange rate indicates competitiveness of domestic producers towards most important trade partners, inflation rate of Slovakia is a proxy for macroeconomic environment and industrial production of the UK stands in for the income variable. The results suggest that export of road vehicles is in the long-run impacted by exchange rate and industrial production. The appreciation of exchange rate reduces export from SR to the UK while rising income increases foreign demand. In the short-run trading with motor vehicles is impacted by all three explanatory variables. The Error correction term indicates that roughly 30 % of disequilibrium in the previous month will be corrected in the current month. The implications are for governing bodies to manage the current commodity framework which is at present mainly oriented on machinery and transport equipment and to support companies from other industries aiming to create more diversified export commodity structure.
Keywords: C01; C03; F01; F14; 330; Export; Road Vehicles; Cointegration; VECM model